Perbaikan Manajemen Kelompok Peternak Sapi Berbasis Kandang Kolektif Di Desa Gelangsar Kecamatan Gunung Sari Kabupaten Lombok Barat - Maya Nachida; Moh. Taqiuddin; I Gusti Lanang Media; Hermansyah; Muh. Prasetyo Nugroho (Universitas Mataram, 2022)
Initiation of mostly the cattle farmer groups in the Village of Gelangsar, the Sub-district of Gunung Sari Sub-district, District of West Lombok was started from the joint practices of keeping their cattle safe in a certain location through Kandang Kolektif. Up to currently, they have an understanding that 'kandang kolektif' is only a keeping place technically for cattle rather than as an institutional for farmers. Indeed, kandang kolektif can be developed as an institutional model to mobilize potentials of cattle-farmers in improving their business productivity. This community service aims to increase knowledge and understanding of cattle farmers, especially Kelompok Muda Mandiri (Independent Young Group) on kandang kolektif-based institutional management including economic analysis of cattle farming through implementation of multiple methods as follows: field observations, in-depth interviews, discussions, and practice. The stages of activities that have been carried out for 12 weeks (3 months) are: analysis of ground problems by observations and interviews with target cattle-farmers; design of problem solving methods; in-class training; technical assistance; and evaluation. The deliverable-results of this community service are: the strengthening of cooperative ties among cattle-farmers; increasing knowledge of cattle-farmers on institutional benefits; they understood the basic concepts of cost-income and was able to calculate the profit-loss of their cattle farming.